2020
DOI: 10.1002/eji.201948391
|View full text |Cite
|
Sign up to set email alerts
|

Antibody, but not B‐cell–dependent antigen presentation, plays an essential role in preventing Chlamydia systemic dissemination in mice

Abstract: The obligate intracellular bacterium Chlamydia trachomatis causes the most prevalent bacterial sexually transmitted infection worldwide. CD4 T cells play a central role in the protective immunity against Chlamydia female reproductive tract (FRT) infection, while B cells are thought to be dispensable for resolution of primary Chlamydia infection in mouse models. We recently reported an unexpected requirement of B cells in localChlamydiaspecific CD4 T-cell priming and bacterial containment within the FRT. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Circulating immunity induced after IN immunization consisted of both antigen-specific CD4 T cells and IgG antibodies, and recent studies point to an important role for antibody in Chlamydia protection (20,21). Local secretion of Cm-specific IgG was detected in the FRT after IN immunization, and the injection of serum into the vaginal vault efficiently blocked infection.…”
Section: Discussionmentioning
confidence: 98%
“…Circulating immunity induced after IN immunization consisted of both antigen-specific CD4 T cells and IgG antibodies, and recent studies point to an important role for antibody in Chlamydia protection (20,21). Local secretion of Cm-specific IgG was detected in the FRT after IN immunization, and the injection of serum into the vaginal vault efficiently blocked infection.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, functioning MHC class-II restricted CD4 T cell responses are the primary requirement for bacterial clearance. In marked contrast, gene-deficient mice lacking MHC class-I or B cells resolve primary Chlamydia infection [ 13 , 17 ], although systemic infection has been detected in B cell-deficient mice before clearance occurs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…PmpD is an attractive vaccine candidate for the prevention of Ct infections due to its interstrain conserved nature, surface localization, implications in early host-cell interaction, and immunological importance because it is the target of neutralizing antibodies 9 , 12 , 13 . As previously shown, antibodies essentially contribute to the resolution of primary Ct infections, and prevent bacterial systemic dissemination in mice 14 , 15 . Furthermore, studies from antibody-deficient mice revealed the fundamental role played by the humoral immune response in conferring protection against chlamydial genital tract re-infection 16 , 17 .…”
Section: Introductionmentioning
confidence: 62%